Globalization and Digital Economy in Bangladesh: : Prospects, Challenges, and the Road to Transformation - Rahaman, Hasibur; Mridha, Md. Sajal (The Jahangirnagar Review, 2025)
Digital economies are growing across the world as a result of globalization, which has become a potent force behind economic change. The article explores the complex relationship between Bangladesh's digital economy and globalization, emphasizing the potential, difficulties, and routes to long-term, sustainable growth. The paper provides a thorough examination of the relationship between Bangladesh's digital economy and globalization. The article laid the groundwork for comprehending how globalization affects Bangladesh's digital economy by outlining the goals and approach. In order to examine how globalization has shaped the digital landscape, the article also provides the theoretical framework, using ideas such as Wallerstein's World-Systems Theory and Harvey's Global Capitalism Theory. Additionally, it integrates ideas of cultural globalization and network effects to contextualize the transformative potential of digital platforms. This paper examines the advantages and disadvantages of the digital economy, emphasizing topics such improved market accessibility, the expansion of e-commerce, and the rise in digital employment. At the same time, it outlines obstacles such as the digital divide between rural and urban regions, regulatory loopholes, and poor infrastructure. The paper provides a thorough analysis of how globalization affects the digital economy in a developing nation like Bangladesh, thereby addressing a significant gap in the scholarly discourse. It seeks to assist stakeholders in utilizing the advantages of globalization while resolving its drawbacks, guaranteeing Bangladesh's inclusive and sustainable digital future.